Simulation on Fear of Crime Among Public Transport Users in Klang Valley Through Regression Analysis Model - Rohana Sham; Shakerin Ismail; Nik Mastura; Noranita Abdamia; Razieman Mohd Yusoff (International Journal of Supply Chain Management, 2018)
Main results from past studies had indicated that level of fear indication is affected by a wide range of elements such as bus service, infrastructure and social environment where travelling took place. However, what is less explored is that how these this travel satisfaction is not only an outcome of travel-related preferences and choices, but that travel satisfaction can act asalso be a predictor of travel-related fear.components. ThusIn thisis conceptual paper we tend to fill the gaps in the existing field of study by examining each of the significant factors that relates to feeling of fear among urban commuters especially for female commuters who live and travel by public bus in urban areas. albeit rather fragmented literature concerning travel satisfaction The paper provide . We provide an overview of the elements explaining on how different level travelof travel satisfaction, can and possibly affect the level of fear le outcomes of travel satisfaction, with a focus on on two extreme condition, (i) subjective well-beingvery satisfied, (ii) very dissatisfied.travel mode choice, (iii) travel-related attitudes, and (iv) the residential location. Furthermore, we suggest a continuous cyclical process including the four above This model highlight a few elements mentioned elements in which travel satisfaction plays an essential role which can results ; a process whichcan result in the formation of of higher or lower level of feartravel habits. This paper will discuss purely on the research methods used in this study where major independent and dependent variable of the study will be discusses especially on the fear detector model being generate through multiple regression analysis. The main focus is on the simulation and evaluation of the model model produced to measure the different level of fear indication based on the different level of satisfaction.